2012
DOI: 10.1039/c2em10806b
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of mould damaged building materials—efficiency of a broad spectrum of treatments

Abstract: We compared the efficiency of some commercially available products and methods used for remediation of mould-contaminated building materials. Samples of gypsum board and pinewood were artificially contaminated with toxin-producing isolates of Stachybotrys chartarum and Aspergillus versicolor, respectively, then, ten different remediation treatments were applied according to the manufacturers' instructions. Microbial and chemical analyses of the infested materials were carried out both immediately before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…When molds develop on surfaces, extensive environmental remediation and replacement of the infected materials is recommended for their removal. The use of a chemical treatment reduces exposure to molds and their byproducts (the mycotoxins), although it does not eradicate them [ 50 ]. The effectiveness of each remediation approach in improving health outcomes must be supported by epidemiological studies, and to the author’s best knowledge, almost all data on the effectiveness of extensive remediation methods were evaluated here [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…When molds develop on surfaces, extensive environmental remediation and replacement of the infected materials is recommended for their removal. The use of a chemical treatment reduces exposure to molds and their byproducts (the mycotoxins), although it does not eradicate them [ 50 ]. The effectiveness of each remediation approach in improving health outcomes must be supported by epidemiological studies, and to the author’s best knowledge, almost all data on the effectiveness of extensive remediation methods were evaluated here [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, it is often difficult and expensive to test environments and items that have been exposed to those environments for mycotoxin contamination [4] and consequently this testing is often not done. Research has shown that none of the commonly used methods for cleaning water-damaged materials such as bleach, ammonia, ultraviolet (UV) light, heating, and ozone were found to completely remove mold and mycotoxins from water-damaged building materials [113]. For this reason, it is safest for patients who have become ill after exposure to water-damaged environments is to avoid exposure to items that were present in the contaminated environment.…”
Section: Avoidance and Total Load Reductionmentioning
confidence: 99%
“…Unfortunately, common building remediation techniques have not been found to be successful in removing mold and mycotoxins from contaminated materials [113]. In this study, pine and gypsum were deliberately contaminated with Stachybotrys chartarum and Aspergillus versicolor and treated with either peroxide, hot air, flaming, two types of boron-based chemicals, drying, steam, UV light, ammonium chloride, or sodium-hypochlorite-based chemicals.…”
Section: Avoidance and Total Load Reductionmentioning
confidence: 99%
“…The material, visually clean and dry, was cut into 2 by 5-cm pieces and then sterilized by autoclaving at 121°C for 20 min before use (27,46). Fungal strains.…”
Section: Mycotoxinmentioning
confidence: 99%